164PMulti-centered phase II trial of weekly 5-FU plus l-LV regimen as salvage line chemotherapy for oral fluorouracil resistant advanced gastric cancer (HGCSG1502). (24th November 2019) - Sasaki, Y; Muranaka, T; Kawamoto, Y; Sawada, K; Nakatsumi, H; Harada, K; Miyagishima, T; Hatanaka, K; Dazai, M; Ueda, A; Sasaki, T; Shinada, K; et al.
Abstract: Background: 5-Fluorouracil (5-FU) is a key drug in treatment of unresectable advanced gastric cancer (AGC). It is known that intravenous 5-FU and oral fluorouracil have different mechanism as anti-cancer drugs, however, a clinical benefit of intravenous 5-FU after using oral fluorouracil is not clear. Therefore, we planned a prospective study to assess the efficacy and safety of weekly intravenous 5-FU and l-leucovorin(l-LV) in Japanese patients with AGC which was resistant for oral fluorouracil, taxane, and platinum. This encore abstract was previously reported at the ESMO 21st World Congress on Gastrointestinal Cancer 2019; the abstract number was P-176. Methods: This regimen consisted of l-LV 250mg/m 2 /2h iv and 5-FU 600mg/m 2 iv once a week for 6 weeks followed by 2-week rest period, within an 8-week cycle. The primary endpoint was the progression free survival (PFS) rate at 8 weeks. Results: Among the 29 enrolled patients, PFS rate at 8 weeks was 55.2% (95% CI 35.6% to 71.0%), which was higher than 47.5% which is the expected value of the hypothesis, and the lower limit of 95% CI is significantly higher than the threshold which is 23.1%. Grade 3 to 4 hematological adverse events (AE) were as follows; anemia 20.7%, neutropenia 3.4%, and platelet count decreased 3.4%. Grade 3 to 4 non-hematological AE were observed as follows; anorexia 20.7%, fatigue 13.8%, and diarrhea 3.4%. Conclusions: The intravenous 5-FU and l-LV regimen is feasible and could be promising as the salvage line treatment in patients with AGC even if that is resistant for oral fluorouracil, taxane and platinum. Legal entity responsible for the study: The Helsinki Ethical Principles (revised in Oct, 2013) and the Ethical Guidelines for Medical and Health Research involving in Human Subjects in 2014. Funding: Hokkaido Gastrointestinal Cancer Study Group. Disclosure: All authors have declared no conflicts of interest.